A novel approach for automated rhinoceros beetle control in oil palm replanting: pineapple peel-derived pheromone trap - Lailatul Munawaroh; Shabri Putra Wirman; Neneng Fitrya; Romi Fadli Syahputra; Novia Gesriantuti (Jurnal Ilmiah Pertanian, 2023)
Oil palm (Elaeis guineensis Jacq) is a crucial plant for Indonesia's economy, serving as a major non-oil foreign exchange earner. A significant pest affecting oil palm cultivation, especially during replanting, is the rhinoceros beetle (Oryctes rhinoceros L.). Attractant pheromones, derived from pineapples, contain volatile compounds that attract insects. This research aims to develop an automated rhinoceros beetle trap equipped with an automatic pheromone spray system utilizing natural peel pineapple extract. The analysis includes tests for fluid density, spray distribution, and normality. The fluid density of the sample closely resembles that of water (1 g/cm³). Spray distribution results indicate particle sizes (60-112 μm) larger than airborne aerosols (0.001-50 μm). Kolmogorov-Smirnov normality tests reveal mostly normal data distribution, with minor deviations. Overall, this trap exhibits promise as an effective solution for rhinoceros beetle control in oil palm cultivation.